Interfering with the CCL2–glycosaminoglycan axis as a potential approach to modulate neuroinflammation - Gschwandtner, Martha; Piccinini, Anna Maria; Geriza, Tanja; Adage, Tiziana; Kungl, Andreas (Elsevier, 2016)
Multiple Sclerosis, a chronic inflammatory demyelinating disease of the central nervous system, involves an increased expression of monocyte chemotactic protein 1 MCP1-/CCL2. For exerting its chemotactic effects, chemokine binding to glycosaminoglycans (GAGs) is required and therefore this interaction represents a potential target for therapeutic intervention. We have designed an anti inflammatory decoy variant, Met-CCL2 (Y13AS21K Q23R), embodying increased affinity for GAGs as well as knocked out GPCR activation properties. This non-signalling dominant-negative mutant is shown here to be able to displace wild type CCL2 from GAGs by which it is supposed to interfere with the chemokine-related inflammatory response. In vivo, the anti-inflammatory properties were successfully demonstrated in a murine model of zymosan-induced peritonitis as well as in an experimental autoimmune encephalomyelitis, a model relevant for multiple sclerosis, where the compound lead to significantly reduced clinical scores due to reduction of cellular infiltrates and demyelination in spinal cord and cerebellum. These findings indicate a promising potential for future therapeutic development.